2020
DOI: 10.1093/dote/doaa102
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome in infants with esophageal atresia: risk factors in the first year of life

Abstract: Summary Data on neurodevelopmental outcomes of infants born with esophageal atresia (EA) are still scarce and controversial. The aims of our study were to evaluate motor and cognitive development during the first year of life, in patients operated on of EA and to investigate potential risk factors for motor and cognitive development both at 6 and 12 months. This is an observational prospective longitudinal study in a selected cohort of type C and D EA infants enrolled in our follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…At 6 months of age, normal neurodevelopment was found in two longitudinal cohort studies: Gischler et al (BSID-I, ages 6, 12, 18, and 24 months, n = 13) 22 and Francesca et al (Bayley-3, ages 6 and 12 months, n = 82). 34 At 12 months of age, both these studies again found normal motor and cognitive functioning. 22 , 34 Francesca et al found a delay with time.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…At 6 months of age, normal neurodevelopment was found in two longitudinal cohort studies: Gischler et al (BSID-I, ages 6, 12, 18, and 24 months, n = 13) 22 and Francesca et al (Bayley-3, ages 6 and 12 months, n = 82). 34 At 12 months of age, both these studies again found normal motor and cognitive functioning. 22 , 34 Francesca et al found a delay with time.…”
Section: Resultsmentioning
confidence: 81%
“… 34 At 12 months of age, both these studies again found normal motor and cognitive functioning. 22 , 34 Francesca et al found a delay with time. They found a significantly lower median motor score at 12 months, compared with the score at 6 months old ( P = 0.033), but higher cognitive function at 12 months compared with the score at 6 months ( P = 0.000).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, it seems that a cohort of our patients, who had undergone median/major neonatal/infantile surgery up till 3 months of age for diverse abdominal, urogenital and other congenital non-cardiac abnormalities, has similar long-term behavioral outcome at mean 4.3 years of age as an omni-cultural general population. It is worth mentioning, though, that our studied patient cohort did not include children who had suffered such severe pathologies as esophageal atresia or diaphragmatic hernia, which had been associated with worse outcome in certain neurodevelopmental domains in previous studies [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This sample, though, must adequately represent the specific population intended to be studied [40]. We did not include children who had surgeries for esophageal atresia, congenital diaphragmatic hernia, or ear, throat, nose abnormalities, conditions that had been associated with worse long-term outcome previously [23,24,41]. Thus, our studied patients had surgeries for anomalies or diseases that do not directly interfere with respiratory, cardiovascular or central nervous system, and abdominal or urological malformations were predominant.…”
Section: Limitationsmentioning
confidence: 99%